Вибір методу розподілу спільних повних енергетичних витрат у комбінованому виробництві енергоносіїв та застосування його на прикладі вугільної ТЕЦ - Horskyi V.V. (General Energy Institute of the National Academy of Sciences of Ukraine, 2021)
Cogeneration of electric and heat energy is a trend in the modern development of energy production systems in the world. The share of electricity produced by CHP in Ukraine coincides with the share of combined heat and power produced by the G8 + 5 countries and is equal to 11–19%. The fuel's heat utilization rate reaches 75% at CHP in the EU countries.An important energy efficiency indicator, characterizing the full technological cycle of power generation, is the total power intensity of the product. To determine the technical and economic indicators of CHP's operation, the production cost of energy products produced, reasonable tariffs for them, and the payback period of investments, first of all, it is necessary to develop a certain scheme for the allocation of costs for each output product.One of the most important methodological issues in combined energy production is the optimal distribution of expenses between the generation and transmission of electric and thermal energy. So far, there are a number of methods for allocating costs by type of product in cogeneration. All methods give different calculation results, and the discrepancy among them is quite significant. Analyzing and comparing them, one can identify both the advantages and disadvantages of each method, depending on the calculation task. The total energy intensity of energy products output for the station was also calculated, and the distribution of energy consumption between thermal and electric energy was performed according to four methods.As a result of the analysis, the thermodynamic method of cost allocation for the supply of electricity and heat is recommended for use, as it takes into account the value of steam used in the turbine (for electric power generation) and is further supplied for the needs of heat supply.